Biological activity tuning of antibacterial urotropine via co-crystallization: synthesis, biological activity evaluation and computational insight. Issue 20 (6th May 2020) - Tabassum, Nida; Varras, Panayiotis C.; Arshad, Fiza; Choudhary, Muhammad I.; Yousuf, Sammer
Abstract : Urotropine (1 ) is a synthetic heterocyclic antibacterial agent. Abstract : Urotropine (1 ) is a synthetic heterocyclic antibacterial agent. We have synthesized co-crystals of urotropine (1 ) with syringic acid, 4-[4-(trifluoromethyl)phenoxy]phenol, and trans -cinnamic acid in a 1 : 1 stoichiometric ratio by using the neat grinding method. The structures of synthesized co-crystals 2–4 were studied via FT-IR spectroscopy, thermal analysis, density functional theory calculations and single crystal X-ray diffraction techniques. In vitro biological activity evaluation indicated that co-crystals 2–4 are potential urease inhibitors and anti-leishmanial agents. Co-crystals 2 (IC50 = 6.5 ± 0.31 μM) and 3 (IC50 = 19.9 ± 0.75 μM) appeared as potent urease inhibitors, whereas co-crystal 4 (IC50 = 34.0 ± 2.13 μM) showed a significant urease inhibition activity against the tested standard acetohydroxamic acid (IC50 = 20.3 ± 0.43 μM). Furthermore, co-crystal 2 (IC50 = 34.27 ± 1.2 μg mL −1 ), co-crystal 3 (IC50 = 22.78 ± 2.8 μg mL −1 ), and co-crystal 4 (IC50 = 24.82 ± 1.4 μg mL −1 ) exhibited significant anti-leishmanial activity in comparison to standard drugs, amphotericin B (IC50 = 0.39 ± 0.05 μg mL −1 ) and pentamidine (IC50 = 3.15 ± 0.005 μg mL −1 ). All synthesized co-crystals 2–4 were found to be non-cytotoxic against the 3T3 normal fibroblast cell line. To the best of our knowledge, the synthesis of co-crystals 2 and 3, and the biological activities of all the synthesized co-crystals 2–4 are reported here for the first time.